EFEKTIVITAS KEBIJAKAN PEMBERDAYAAN USAHA MIKRO KECIL DAN MENENGAH (SUATU STUDI DI KECAMATAN KAWANGKOAN UTARA) - Wonok, Yolanda; Tulusan, Femmy; Ruru, Joorie (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT:Empowerment of small and medium micro enterprises is one of the policies made by the Indonesian government in improving the welfare of society. and in accordance with law no.20 of 2008 regulates micro, small and medium-sized businesses, as well as by government regulation no. 13 of 2013 on the implementation of law No. 20 of 2008, the government made a policy regarding the development programs of small and medium micro enterprises. Policy pursued by the government in improving the empowerment of micro, small and medium enterprises are the government gave permission for business in running a certain business activities; business development through the provision of facilities, coaching and mentoring; assistance to foster and improve the capabilities and competitiveness of businesses; coordination and control of the government. Small and medium micro policies have also been imposed by the government in the district of northern Kawangkoan. Problems to be answered in this research is how the effectiveness of the empowerment of small and medium micro enterprises in Kawangkoan northern districts. This study used qualitative methods, this study aimed to describe, analyze and determine the effectiveness of the empowerment policy of small and medium micro enterprises. Results of research conducted by collecting data obtained through observation and interviews based on several indicators, as follows: (1) Responsiveness, (2) Development, (3) Adequacy. Based on the results of the study conclude that the policy of empowerment of micro, small and medium-sized enterprises in the district north Kawangkoan already quite effective. Based on the conclusion of the study, it is suggested to Kawangkoan northern district government to pay more attention to the needs of the micro business small and medium in increasing empowerment of small and medium micro enterprises. Key words: effectiveness, policy, empowerment.